PENGARUH KUALITAS LAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN PADA PT. HADJI KALLA PALU - Pangandaheng, Fony (Katalogis, 2015)
The objectives of this research are: 1) to know and analyze the effect of service quality on corporate image,2) to know and analyze the effect of service quality on customer satisfaction. 3) to know and analyze the effect of corporate image on customer satisfaction, 4) to know and analyze the effect of customer satisfaction on customer loyalty. This is an explanatory research to explain the relationships among investigated variables involving 150 customer of PT. Hadji Kalla Palu that have been selected using purposive technique sampling. Based on the hypotheses testing using of Structural Equation Modeling (SEM), it concludes that: 1) service quality performs positive and significant effect on corporate image;2) service quality performs positive but not significant effect on customer satisfaction; 3) corporate image performs positive and significant effect on customer satisfaction; 4) customer satisfaction performs positive and significant effect on customer loyalty.